Lipidomic Profiling Reveals HSD17B13 Deficiency-Associated Dysregulated Hepatic Phospholipid Metabolism in Aged Mice - Cong Zhang; Yingxin Feng; Xiaoyan Zhang; Youfei Guan; Wen Su (Metabolites, 2025)
Objectives: HSD17B13 (17β-hydroxysteroid dehydrogenase 13), a lipid droplet-associated enzyme, has emerged as a key regulator of hepatic lipid metabolism and a potential therapeutic target for metabolic-associated fatty liver disease (MAFLD). While its role in lipid homeostasis and liver inflammation has been partially revealed, the impact of HSD17B13 deficiency on lipid metabolism in aged mice remains poorly understood. In this study, we performed comprehensive lipidomic profiling of liver tissues from aged Hsd17b13 gene knockout (Hsd17b13 KO) mice to investigate the effects of Hsd17b13 deletion on hepatic lipid composition and metabolic pathways. Methods: Changes in hepatic lipid profiles were assessed through a liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based lipidomic analysis. Results: The lipid profiles, including triglycerides (TGs), diglycerides (DGs), phosphatidylcholines (PCs), phosphatidylethanolamines (PEs), phosphatidylglycerols (PGs), and ceramides (Cers), exhibited notable alterations in the Hsd17b13 KO mice. Conclusions: HSD17B13 plays a pivotal role in liver lipid metabolism during aging, and it is involved in the regulation of hepatic phospholipid metabolism. Our study highlights the importance of HSD17B13 in maintaining liver lipid homeostasis and its potential as a therapeutic target for age-related liver diseases.